Kinetics of the coefficient of friction of elastomers; Scientific Reports; Vol. 4 - Qiang Li; Dimaki A. V. Andrey Viktorovich; Popov M. Mikhail; Psakhie S. G. Sergey Grigorievich; Popov V. L. Valentin Leonidovich (2014, 2014)
Title screen